Gene therapy strategies for dominant heterogeneous disorders and the identification of a novel gene causing retinitis pigmentosa and sensorineural deafness - Millington-Ward, Sophia (Trinity College (Dublin, Ireland). Department of Genetics, 2000)
The purpose of this Ph.D. thesis has been to contribute towards the generation of therapies for inherited disorders such as retinitis pigmentosa (RP) and osteogenesis imperfecta (OI). In chapter 2, a novel mitochondrial disease mutation in the second serine tRNA gene (MTTS2) was discovered and characterised. A heteroplasmic C->A transversion at position 12258 in MTTS2 was found to cause RP in conjunction with sensorineural deafness in a large Irish kindred (Kenna et al., 1997; Mansergh et al., 1999) This study highlights yet again, the genetic heterogeneity present in many inherited disorders such as RP (Appendix B and table 2, chapter 1).
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin